Pengaruh Kompetensi Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Perikanan Kabupaten Pesisir Barat - Yani, David Ahmad; Meidasari, Evi (Jurnal Manajemen dan Bisnis (JMB), 2025)
AbstractCompetence is the ability of an employee to carry out tasks. Work motivation is an encouragement that comes from the employee. Performance is the result of work both in quality and quantity. This study aims to determine the effect of work competence and motivation on employee performance at Dinas Perikanan Kabupaten Pesisir Barat.The research conducted was quantitative descriptive research. This study used 56 research respondents. There are three variables in this study, namely: 2 (two) independent variables (X1 and X2) and 1 (one) dependent variable where competence (X1) and work motivation (X2) are independent variables and employee performance (Y) as the dependent variable.From the results of data processing, the following hypothesized answers have been found; there is the influence of competence (X1) on employee performance (Y), with a level of influence of 65.7% There is an influence of work motivation (X2) on employee performance (Y) with a level of influence of 70.8%. There is an influence of competence (X1) and work motivation (X2) together on employee performance (Y), with a level of influence of 77.2%. Keywords : Competence, work motivation, employee performance